PROPERTY RESTITUTION IN LITHUANIA, AN REPARATORY TOOL IN THE PROCESS OF TRANSITIONAL JUSTICE? - Bianca Elena RADU (Challenges of the Knowledge Society)
In Lithuania, the 90s marked the beginnings of a transitional period toward the reconstruction of a democratic state. On the one hand, it emerged as the ideal model, a new societal and state project, a democratic society, with a state founded on respect for the law and for human rights. On the other hand, the past made its presence felt as a result of administrative and judicial heritage, but also of a pattern socially reproduced at the level of human interactions between those whose rights were violated and those who violated these rights. Among those whose rights were abusively violated in the old regime were those dispossessed of properties and of their right over them, during the communist period. The old regime’s abusive seizing of properties was a prejudice brought to the dispossessed. The present paper intends to analyse whether property restitution in Lithuania was part of a more extensive process, entitled transitional justice in the literature. The first part of the paper describes the theoretical lens as well as conceptual aspects. The second part focuses on property legislation and on the function laws fulfilled in the reparations process. The paper has a heuristic value and constitutes itself as part of the research in the field of transitional justice and property restitution.